Perlindungan Konsumen oleh Otoritas Jasa Keuangan Terhadap Nasabah Asuransi yang Dirugikan - Ahmad Nazori (Universitas Batanghari Jambi, 2021)
Insurance is an institution to invest funds with a specific purpose so that if in the future it is needed by the insurance customer, the funds can be withdrawn by the insurance customer. However, in reality, many insurance customers suffer losses because the funds they have invested in the insurance company are not disbursed by the insurance company. This is the subject of discussion in this study so that the research method is carried out with an analytical approach and a statutory approach. The research materials are primary, secondary and tertiary legal materials so that the data collection techniques use literature studies and qualitative analysis techniques. In this case, discussing the regulation of the duties of the Financial Services Authority in overcoming the occurrence of a loss insurance customers is regulated in Law Number 21 of 2011 concerning the Financial Services Authority, Regulation of the Financial Services Authority Number 1/POJK.07/2013 concerning Consumer Protection Sector Financial Services and OJK Circular Letter Number 2/SEOJK.07/2014 Regarding Consumer Complaint Service and Settlement and consumer protection by the Financial Services Authority for insurance customers who are harmed is that there is no consumer protection carried out by Financial Services cooperatives for insurance customers who are harmed by the company insurance